Evaluation of Apical Root Resorption during Alignment Phase of Fixed Orthodontic Treatment: A Prospective Study - Novaira Waseem, Zubair Hassan Awaisi, Amna Malik (Pakistan Journal of Medical & Health Sciences, 2024)
Purpose: External apical root resorption (EARR) is a permanent shortening of the root apex, often detected through radiographic imaging, characterized by the loss of the protective outer layer.To evaluate the apical root resorption during alignment phase of fixed orthodontic treatment Method: Prospective Study was conducted in the Department of Orthodontic, Nishtar Institute of Dentistry, and Multan from 6th October 2020 to 5th April 2021. The study included a 110 patients aged between 18 and 25 years. The evaluation of External Apical Root Resorption (EARR) was conducted prior to and following the therapy. In order to carry out this assessment, a group of 110 patients underwent periapical radiographs utilizing the paralleling approach. The radiographs were taken at the beginning of the treatment and then again at the conclusion of a three-month research period. Afterwards, the length from the incisal edge to the apex of all incisors was carefully measured using a vernier caliper. The difference in root length, measured in millimeters, between the pre-treatment (T0) and post-treatment (T1) stages was measured and expressed as a percentage of the initial root length. Results: Root resorption may initiate during the initial leveling stages of orthodontic treatment. The age range of these patients was quite broad, as the minimum age observed was 12.0 years, and the maximum age reached 25.0 years. It was noted that 35.45% of the enrolled patients were male, amounting to 39 individuals, while the majority, comprising 64.54%, were female, totaling 71 patients. For the maxillary central incisor on the upper right side, the mean root length before treatment was 17.51mm, which decreased to 16.30mm after treatment. The difference, indicating root resorption, was 1.21mm, with a standard deviation of 3.431. Practical Implication: These results contribute to enhancing the overall safety and efficacy of orthodontic procedures, benefiting patient outcomes. Conclusion: Root resorption was observed in all maxillary incisors to varying degrees, with central incisors experiencing greater resorption compared to lateral incisors. Root resorption can be detected in the initial phases of orthodontic therapy, according to the study. Keywords: Apical Root Resorption, Endodontically Treated, Orthodontic Treatment, Root Apex,